2019
DOI: 10.3390/rs11171987
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Hyperspectral and Geochemical Study of Sediment-Hosted Disseminated Gold at the Goldstrike District, Utah

Abstract: The Goldstrike district in southwest Utah is similar to Carlin-type gold deposits in Nevada that are characterized by sediment-hosted disseminated gold. Suitable structural and stratigraphic conditions facilitated precipitation of gold in arsenian pyrite grains from ascending gold-bearing fluids. This study used ground-based hyperspectral imaging to study a core drilled in the Goldstrike district covering the basal Claron Formation and Callville Limestone. Spectral modeling of absorptions at 2340, 2200, and 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…Hydrothermal alteration mineral assemblages associated with gold mineralization that formed under low to medium temperatures (≤150 • C~300 • C) are deliberated as one of the most significant indicators for epithermal gold exploration [33,34,[87][88][89]. Remote sensing satellite imagery is extensively and successfully used for mapping hydrothermal alteration zones for gold minerals exploration in many metallogenic provinces around the world [7,12,15,[17][18][19][20]36,38,[90][91][92][93][94]. In the Ahar-Arasbaran region, NW Iran, a variety of ore mineralizations such as Au, Cu-Au, Au-Ag, Fe-Au, Cu-Mo, Fe, Cu, Pb-Zn are identified, which are associated with widespread hydrothermal alteration minerals [47,49,51,[95][96][97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal alteration mineral assemblages associated with gold mineralization that formed under low to medium temperatures (≤150 • C~300 • C) are deliberated as one of the most significant indicators for epithermal gold exploration [33,34,[87][88][89]. Remote sensing satellite imagery is extensively and successfully used for mapping hydrothermal alteration zones for gold minerals exploration in many metallogenic provinces around the world [7,12,15,[17][18][19][20]36,38,[90][91][92][93][94]. In the Ahar-Arasbaran region, NW Iran, a variety of ore mineralizations such as Au, Cu-Au, Au-Ag, Fe-Au, Cu-Mo, Fe, Cu, Pb-Zn are identified, which are associated with widespread hydrothermal alteration minerals [47,49,51,[95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Multispectral and hyperspectral satellite imagery with appropriate spatial and spectral resolution is capable of recording the spectral absorption signatures of alteration minerals in the VNIR and SWIR spectral bands, which can be utilized to map and remotely detect hydrothermal alteration mineral zones associated with ore mineraliztions [6][7][8][9]. Recently, the identification of alteration mineral zones using remote sensing sensors is effectively and extensively used for prospecting porphyry copper, epithermal gold, uranium and massive sulfide deposits in metallogenic provinces around the world [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested the combined use of geochemical and hyperspectral data for the interpretation and validation of the results [25], [39], [41]- [44]. For example in [42], the geochemical and hyperspectral data sets are processed and analysed separately and their results are compared and used for a complete understanding and analysis of the correlation between stratigraphic control as well as mineralogical alterations. In [45], the authors proposed a combination strategy and linked hyperspectral and geochemical data to successfully infer geochemical and mineralogical characteristics of an specific rock-type from hyperspectral data.…”
Section: Introductionmentioning
confidence: 99%
“…High spectral resolution of hyperspectral sensors makes it an ideal complementary and confirming tool alongside traditional multi-spectral and field-based methods for mineral exploration [3]. Therefore, reflectance and emission spectroscopy in visible-to-near-infra-red and mid-infra-red have globally been used as an important tool for mineral characterization and exploration [8,20,22,26,32,39,44]. Data collected by imaging spectrometer using geometrically coherent spectral measurements facilitate quantitative and qualitative identification and mapping, thereby allowing a more detailed characterization of the spatial mineralogical heterogeneity using mixture analysis technique [21,[50][51][52][53].With the availability of more sophisticated and high-resolution spectrometers, the field of imaging spectroscopy from space, air or field has grown in terms of technical capability and application potential in geological mapping and mineral exploration [12,13,19,27,33,35,36,43,45,54,56].…”
Section: Introductionmentioning
confidence: 99%